Crust and Upper Mantle Structure of the South China Sea and Adjacent Areas From the Joint Inversion of Ambient Noise and Earthquake Surface Wave Dispersions. (9th March 2021) - Chen, Haopeng; Li, Zhiwei; Luo, Zhicai; Ojo, Adebayo Oluwaseun; Xie, Jun; Bao, Feng; Wang, Liaoliang; Tu, Guanghong
Abstract: In this study, we built a high‐resolution 3D S‐wave velocity model of the South China Sea (SCS) and adjacent areas by the joint inversion of surface wave dispersions retrieved from ambient noise and earthquake data. We first measured Rayleigh wave phase velocity dispersions from the waveforms recorded by 94 broadband seismic stations. Subsequently, we used a generalized least squares inversion scheme with spatially varying resolution to perform 2D tomographic inversion at different periods. Lastly, we performed 1D inversion at different grid points and obtained the 3D S‐wave velocity model in the depth range of 15–250 km. Our model reveals a prominent high velocity (high‐V) anomaly beneath the SCS basin and shows that the lithosphere beneath the SCS basin is about 70–80 km thick. We observe a prominent low velocity (low‐V) anomaly in the asthenosphere beneath the SCS basin, and we interpret this as evidence for the ongoing partial melting of the asthenosphere. An obvious high‐V anomaly is also revealed beneath the Khorat Plateau (KP) in the depth range of 80–150 km, suggesting that the KP has a cold and thick lithosphere and has suffered limited destruction in the Cenozoic era. In the northern part of Kalimantan Island (KI), a prominent low‐V anomaly is shown in the upper 60 km of the lithosphere revealing the upwelling of the asthenosphere. Our findings shed lights on the tectonic evolution of the SCS and adjacent areas. Key Points: A high‐resolution 3D S‐wave velocity model is built in the South China Sea and adjacent areas There is a prominent high velocity anomaly beneath the South China Sea Basin and the lithosphere thickness is about 70–80 km The obvious low velocity anomaly beneath the northern Kalimantan Island may indicate the upwelling of the asthenosphere